Post-Covid Media Behaviour Patterns of the Generation Z Members in Slovakia - Lesková, Andrea; Lenghart , Patrik (Journal of Education Culture and Society, 2023)
Aim. The aim of the article is to identify and describe internet-consumption behavioral patterns that have been common after the Covid-19 restrictions have been lifted. Concept. In July 2022, we conducted a quantitative research based on an online survey in which 800 members for the Slovak Generation Z participated. Results. The results indicate a notable decrease in the quantity of time the Slovak Generation Z members spend daily online, when compared to the time of the Covid-19 pandemic, but the average daily time spent online never returned to the numbers typical for the pre-Covid times. Conclusion. Our data are an asset to the general knowledge base about the Slovak Generation Z internet-consumption behavioral patterns, but they are also specifically relevant for the disciplines of marketing, and mass-media communication, that view the Generation Z cohort as a part of the global audience. Cognitive value. The article contributes to the growing knowledge-base about the internet-consumption behavioral patterns of the (Slovak) Generation Z, and as such could be valuable for building theories about this part of the audience between the years 2020 and 2030, which will be a pivotal time for the development of marketing, internet and mass-media communication and the changes that will occur along with the change of the dominant position from the Generation Y to Generation Z, when it comes to the influence on the world’s mass-media markets, but also in other segments.